(sinx+tgx) * (cosx+ctgx) = (1+sinx) * (1+cosx)

Trigonometry equalities, inequalities and expressions - sin, cos, tan, cot

(sinx+tgx) * (cosx+ctgx) = (1+sinx) * (1+cosx)

Postby Guest » Tue Oct 16, 2018 8:25 pm

(sinx+tgx) * (cosx+ctgx) = (1+sinx) * (1+cosx)
Guest
 

Re: (sinx+tgx) * (cosx+ctgx) = (1+sinx) * (1+cosx)

Postby nathi123 » Wed Oct 17, 2018 1:55 pm

[tex]A = ( sinx+tgx)(cosx+cotgx) = (sinx+\frac{sinx}{cosx})(cosx+\frac{cosx}{sinx})=sinxcosx(1+\frac{1}{cosx})(1+\frac{1}{sinx})\Leftrightarrow[/tex]
[tex]A=\frac{sinxcosx}{sinxcosx}(1+cosx)(1+sinx) =(1+cosx)(1+sinx)[/tex] .

nathi123
 
Posts: 21
Joined: Sun Sep 17, 2017 1:56 pm
Reputation: 19


Return to Trigonometry - sin, cos, tan, cot, arcsin, arccos, arctan, arccot



Who is online

Users browsing this forum: No registered users and 1 guest